A serviceability investigation of dowel-type timber connections featuring single softwood dowels. (1st June 2022) - Wilkinson, George; Augarde, Charles
Highlights: Modelling of dowel-type connections in timber is feasible with commercial FE software. Results show the effect of timber properties on slip modulus. Study provides guidance on effect of connection angle absent from Eurocode. Results indicate potential for study of other dowel types and arrangements. Abstract: Dowel-type connections are common in timber engineering, but current design codes are largely based on empiricism and are oversimplified. This inhibits the optimised use of connections, which is essential for the design of economically efficient timber structures. This study investigates the use of 3D computational modelling to predict the slip modulus (a key measure of stiffness) of single and double shear, dowel-type connections featuring a single softwood dowel. Initial modelling was conducted on parallel- and perpendicular-to-grain connections to establish a suitable mesh size and to validate the model against experimental work. The slip modulus in angled orientations was then investigated, a relationship given no consideration in design codes. The results show that the current design codes greatly overestimate the slip modulus in both single and double shear connections involving timber dowels. In comparison, the models in this study are more than twice as accurate at predicting slip modulus. Furthermore, slip modulus was shown to vary sinusoidally as the grain-to-grain angle changes between the parallel and perpendicular orientations. Differences between model and experimental values can be attributed to uncertainty in the mechanical properties of the timber in the experiments, the assumption of uniform properties for timber in each principal direction in the models, and the inherent variability of timber which affects experimental results.